2022
DOI: 10.1007/s12528-022-09333-2
|View full text |Cite
|
Sign up to set email alerts
|

The relations between self-reported perceptions of learning environment, observational learning strategies, and academic outcome

Abstract: This study investigated the relations between students’ self-reported perceptions of the blended learning environment, their observed online learning strategies, and their academic learning outcomes. The participants were 310 undergraduates enrolled in an introductory course on computer systems in an Australian metropolitan university. A Likert-scale questionnaire was used to examine students’ perceptions. The digital traces recorded in a bespoke learning management system were used to detect students’ observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Additionally, it is worth noting that the scales were designed differently, adding another layer to interpreting the results. Looking at virtual learning, Han and Ellis (2023) discovered that students with more positive perceptions of the learning environment tended to exhibit better academic performance. The interrater reliability was weak or nonexistent in roles and responsibilities, collaborative patient-/family-centered approach, and conflict management.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is worth noting that the scales were designed differently, adding another layer to interpreting the results. Looking at virtual learning, Han and Ellis (2023) discovered that students with more positive perceptions of the learning environment tended to exhibit better academic performance. The interrater reliability was weak or nonexistent in roles and responsibilities, collaborative patient-/family-centered approach, and conflict management.…”
Section: Discussionmentioning
confidence: 99%
“…The online learning environment plays a crucial role in tailoring students' learning experiences based on individual preferences. Research has shown that students' perceptions of the blended learning environment significantly impact their academic outcomes (Han & Ellis, 2023). Additionally, the Community of Inquiry (CoI) framework highlights the interaction of individual elements with the broader environment, emphasizing the importance of considering macro and meso levels in online learning (Arifeen, 2023).…”
Section: Adaptability and Personalizationmentioning
confidence: 99%